2021
DOI: 10.3233/shti210741
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Informatics Research Trends: Findings from an International Survey

Abstract: This follow-up survey on trends in Nursing Informatics (NI) was conducted by the International Medical Informatics Association (IMIA) Student and Emerging Professionals (SEP) group as a cross-sectional study in 2019. There were 455 responses from 24 countries. Based on the findings NI research is evolving rapidly. Current ten most common trends include: clinical quality measures, clinical decision support, big data, artificial intelligence, care coordination, education and competencies, patient safety, mobile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“… 40 In fact, in a 2013 priority list for NI research, integrating genomic data into the EHR was last in a list of 20 research topic areas; no other epigenetic research-related topics were included in the priority list, and a 2021 study listed genomics as 32 of a 36-item priority research list. 41 , 42 Among other priorities of NI research listed were clinical decision support (#2 on the 2021 list), Big Data (#3 on the list), and data science (#25 on the list), all of which are components of genomic and epigenetic research. Nursing informatics theory got a higher priority (#30 of 36) than genomics, indicating that some NI researchers are focusing on topics that do not put the patient at the center of data analysis or NI research.…”
Section: Current Statementioning
confidence: 99%
“… 40 In fact, in a 2013 priority list for NI research, integrating genomic data into the EHR was last in a list of 20 research topic areas; no other epigenetic research-related topics were included in the priority list, and a 2021 study listed genomics as 32 of a 36-item priority research list. 41 , 42 Among other priorities of NI research listed were clinical decision support (#2 on the 2021 list), Big Data (#3 on the list), and data science (#25 on the list), all of which are components of genomic and epigenetic research. Nursing informatics theory got a higher priority (#30 of 36) than genomics, indicating that some NI researchers are focusing on topics that do not put the patient at the center of data analysis or NI research.…”
Section: Current Statementioning
confidence: 99%
“…Based on standardized data on patient history and nursing assessment results, clinical decision support (CDS) is made available to accomplish meaningful use of EHR and to assist health care professionals with decision-making [ 3 ]. SNL and CDS are among the top research priorities in nursing informatics [ 4 ]. Despite its potential to support and transform nursing practice by simplifying record-keeping, promoting standards-based practice, and giving timely access to information to aid decision-making [ 5 ], the introduction of NIS, does not necessarily lead to user adoption [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additional evidence on nursing informatics (NI; Peltonen et al, 2016;Topaz et al, 2016) The literature adopted for this article was identified adopting the guidance of a modified 'argumentative literature review' methodology as developed by McCullough et al (2004) for evaluating topics while examining literature selectively in order to support or refute an argument. The purpose of this approach to literature review is to develop a body of literature that establishes a contrarian viewpoint.…”
Section: Introductionmentioning
confidence: 99%